Resistensi Masyarakat Terhadap Pemecatan Sepihak Secara Masal Oleh PT. Pinago Utama Musi Banyuasin (Studi Kasus Perlawanan Masyarakat Desa Mangun Jaya, Musi Banyuasin) - Muhammad Atila Dafa Valentino Ramadhan; Ainur Ropik; Deany Afriany (CV. ITTC INDONESIA, 2025)
This study addresses the complex industrial conflict in Mangun Jaya Village, which arose from unilateral mass layoffs by PT. Pinago Utama. The discontent was triggered by a management change that introduced oppressive policies, the unfair implementation of a fingerprint system, the imposition of burdensome integrity pacts, inequities in compensation and facilities, and the threat of losing their sole livelihood for a community heavily reliant on plantation work. The research aimed to analyze the forms of resistance adopted by the community, identify the factors driving this resistance against PT. Pinago Utama's policies, and evaluate the role of the government in mediating the conflict. Employing a qualitative research method with a case study approach, in-depth interviews with key informants (PT. Pinago workers, ex-employees, and local community leaders) and field observations were conducted for primary data collection. Secondary data was gathered from relevant documents such as company reports and Manpower Office data, and thematic descriptive analysis was applied. The findings indicate that the community's resistance manifested as open defiance, strengthened by social solidarity among workers and support from civil society organizations and local figures. From James C. Scott's resistance theory perspective, this represents a struggle to maintain dignity, identity, and livelihood amidst an unequal power structure. The government's role, particularly through the Manpower Office, in mediating this conflict remained largely symbolic and limited to facilitation. The government tended to be neutral and passive, failing to substantively protect workers' normative rights, which highlights a lack of political will and partiality in enforcing social justice.